Pathways of Metastases from Primary Organs to the Ovaries - Yukio Yamanishi; Masafumi Koshiyama; Megumi Ohnaka; Masashi Ueda; Shingo Ukita; Kenji Hishikawa; Michikazu Nagura; Tomoko Kim; Masaya Hirose; Hiroshi Ozasa; Tomoyuki Shirase (Obstetrics and Gynecology International)
To investigate the metastatic pathways from the primary organs to the ovaries, we examined the microscopic findings from 18 original and 18 metastatic ovarian tumors carefully. In addition, we examined the immunohistochemical findings (Victoria blue stain for vascular invasion and D2-40 expression for lymphangio invasion) of metastatic ovarian tumors carefully. There were 4 (57%) ovarian lymphangio invasion cases in the 7 gastric cancers, but there were no cases in the 6 colorectal cancers (P < 0.05). There were 4 (67%) ovarian vascular invasion cases and one (17%) liver metastasis case in the 6 colorectal cancers, while there were no ovarian vascular invasions (P < 0.05) or no liver metastases in the 7 gastric cancers. The patients with metastatic ovarian tumors originating from distant organs who were treated at the same time as the original cancers had a significantly poorer prognosis than the patients with ovarian tumors treated later (P < 0.05). The rate of lymphatic metastasis from the stomach to the ovary was significantly higher than from the colon to the ovary. In addition we hypothesized that the rate of intravascular metastasis from the colorectum to the ovary was relatively higher than from the stomach to the ovary.